The promotion of family sheep-farming in Mexico through subsidies in assets: lessons learned. - Martínez-González, Enrique Genaro (2011)
The objectiveof this work was to determine the impact of subsidies givenin assets for the purchase of productive actives in familiarsheep production units (UPF) in the state of Mexico.A survey was carried-out among 58 sheep farmers in apopulation of 475 benefi ciaries, from January to Marchof 2007. Seventeen months after subsidy release, 16% ofUPF were closed, 48% were stable or growing, and 36%were contracting. Herd dynamics could be explained onthe basis of previous experience of the sheep farmer, thecapacity of the UPF to produce the feed required by theherd, the adoption of new innovative and good practices theproduction system, the network of knowledge to which thefarmer belongs, the sheep quality offered by the network oflivestock providers; and the conception of the activity ofthe producer himself, as savings or as a business. Subsidiesdirected to this activity did not increase productive capacityof the herds, and did not generate wealth or employment.